The life history, habits and some aspects of the natural control of Choristoneura Fumiferana (Clemens) (Lepidoptera : Tortricidae) in Newfoundland - Crummey, Hubert Ralph (1976)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1976. Biology Bibliography: leaves 101-106.